Hippocampal synaptotagmin-4 is correlated with impaired spatial learning and memory in SAMP8 mice. (21st October 2015) - Yang, Qi-Gang; Chen, Gui-Hai; Wang, Fang; Wang, Long-Hai
Highlights: Age-related deficits of spatial learning and memory in SAMP8 mice were evaluated. Syt-1 and Syt-4 levels in different dorsal hippocampus layers were detected. Correlations between Syt-1/Syt-4 levels and spatial performance were explored. Altered Syt-1 and Syt-4 levels with age may be involved in cognitive deficits. Abstract: The mechanism underlying age-related cognitive impairment remains unclear. To determine whether synaptotagmin (Syt)-1 and Syt-4 are involved in age-related cognitive impairment, we used a radial six-arm water maze (RAWM) to evaluate spatial learning and memory deficits in the senescence accelerated prone mouse 8. The Syt-1 and Syt-4 levels of different subregions of the dorsal hippocampus (DH) were detected through immunohistochemistry. The RAWM results revealed that 13- and 9-month-old mice exhibited longer latencies and more errors in both the learning and memory phases than 5-month-old mice. Similar results were observed in the comparison of 13-month-old mice to 9-month-old mice. Compared with the 9- and/or 5-month-old mice, the 13-month-old mice exhibited higher Syt-1 and Syt-4 levels in the majority of the DH subregions with the exception of Syt-1 in the dentate gyrus-hilus and Syt-4 in the dentate gyrus-hilus and cornu ammonis 1 pyramidal cell layer. With the exception of Syt-1 in the 9-month-old mice, the Syt-1 and Syt-4 levels in several DH subregions overall and in each group were significantly correlated with the performances on the RAWM. Therefore, the altered Syt-1 and Syt-4 levels in the different DH layers may have been involved in the impairments in spatial learning and memory during normal aging.